The role of TGFβ in human cancers - Wong, Shew-Fung; Lai, Leslie C. (Elsevier, 2001)
Transforming growth factor β (TGFβ) is secreted as a large latent precursor from both normal and transformed cells which needs to be activated for biological activity. The active TGFβ binds either directly to TβR-II or indirectly by binding to β-glycan which then presents the TGFβ to TβR-II. Formation of the TGFβ-TβR-II complex rapidly leads to phosphorylation of TβR-I. TβR-I, in turn, phosphorylates receptor-specific Smads and induces their translocation into the nucleus. TGFβ is able to act as a growth stimulator or inhibitor and elicits a broad spectrum of biological, effects on various cell types. However, these cells may lose their sensitivity and responsiveness to TGFβ. Down-regulation or loss of functional receptors, aberrant signal transduction pathways due to Smad mutations, loss of the cell's ability to activate latent TGFβ, loss of the peptide itself or functional genes that control the transcription and translation of TGFβ may contribute to development of cancer.